The Role of Ethnography in the Analysis of Phrases and Units (Eurasian Journal of Humanities and Social Sciences, 2023)
This article analyzes French phrases and phraseological units by comparing and learning the opinions of linguists. In the research phrases used in the speech process and to help enrich the language are translated into uzbek and the definition are given.